A New Type of DC-DC Buck Converter with Soft Start Function and Reduced Voltage Stress - Xin Wang; Zishuo Li; Zhen Lin; Fanyi Meng (Journal of Low Power Electronics and Applications, 2025)
This paper introduces a novel topology called the dual-path step-down converter with auxiliary switches to minimize voltage stress and enable wide voltage conversion ranges. The proposed dual-path step-down converter with auxiliary switches, which uses an inductor and flying capacitor as power conversion components, helps to reduce the voltage stress on the power switches. By adding auxiliary switches, the proposed topology achieves the same voltage conversion ratio range as that of a conventional buck converter. Additionally, soft-start technology is incorporated to reduce the initial inrush current. Furthermore, this paper introduces a system-level design procedure for DC-DC converters. Designed for low-power applications with lithium-ion (Li-ion) batteries, the proposed converter steps down the battery voltage to 1.2 V. With a 380 nH inductor and a 5 µF output capacitor, the converter attains a peak efficiency of 90% under the conditions of 2.7 V to 1.2 V conversion.